FATWA ‘ATHIYYAH SHAQAR (PEMIKIRAN TOKOH HUKUM ISLAM MESIR) - Taufid Hidayat Nazar (UIN Imam Bonjol Padang, 2018)
Fatwa in general refers to the legal opinion issued by any Muslim jurist(mufti) relating to certain rulings of Islamic law. In principle, fatwa serves asa means of clarifying any issue that arises in Muslim society. This reflects thatfatwa and mufti are two crucial significant tools of providing legal guidancewithin the ambit of the Shari'ah governing Muslims in their day-to-day affairs.However, there are some contemporary scholars whose fatwas are approvedby state institutions and governments local. Still, there is no clarity on theirthoughts and methods of the ijtihad in issuing their fatwas. One of the scholarsmentioned is 'Athiyyah Shaqar, a senior mufti from Egypt. This paper seek tospecify the maps of Islamic Legal Thought of ‘Athiyyah Shaqar, especially inthe mujtihad level, and most importantly, this paper analyzed the methods of'Athiyyah Shaqar in answering the three contemporary fatwas; 1) Zakah tohelp in marriage expenses 2) Radhâ laws of breast milk bank 3) Femalegenital mutilation laws. Furthermore, the approach used was characteranalysis patterened with literatur study. The results, ‘Athiyyah Shaqar'sposition of thought in Islamic law is not as a mujaddid. In the context of themujtahid level which has been an important study in the literacy of usul fiqh,‘Athiyyah Shaqar is at the level of Mujtahid Murajjih.